Affect, disposition, and cognition in motivation: linking them back together - Neilson, J. Ragan Ward, author (Colorado State University. Libraries, 2005)
In modem motivation literature, studies of the affective and dispositional components of motivation have been relatively scarce. Therefore, this study examines how motivational traits and mood jointly influence the self-selection of level of goal difficulty. The participants (N = 294,73% female, 84% Caucasian) were undergraduate students from a large public university in the western United States. The Motivational Trait Questionnaire (MTQ) was administered as a measure of trait motivation. Participants' moods were measured with the PA scale of the Positive and Negative Affect Schedule (PANAS). Participants were introduced to a problem-solving task and asked to self-set goals for their performance on this task. Results of the analyses indicated that personal mastery and competitive excellence were positively correlated with self-set level of goal difficulty, while motivation anxiety was uncorrelated with self-set level of goal difficulty. PA was positively correlated with the self-set level of goal difficulty. Moderated regression analyses revealed that PA moderated the relationship between competitive excellence and self-set level of goal difficulty; however, the nature of this interaction was not as predicted. The results indicated that as PA increased the relationship between competitive excellence and self-set level of goal difficulty decreased. The limitations and conclusions of this study are discussed.